PERFORMANCE IMPROVEMENT OF SAC USING NEW EMD AND MD BASED 2D-OCDMA - Hamza Mumtaz; Khalid Rehman; Kiran Raheel; Adil Nawaz; Hashim Ali (Spectrum of Engineering Sciences, 2025)
The adaptability of a passive optical network necessitates the employment of an appropriate multiple-access method that can offer the requisite transmission capacity in terms of data, reach, and number of users while being simple to construct and low in cost. Because of its asynchronous nature and simultaneous access to the channel for different users, the spectral amplitude coding- photonic code division multiple access system is expected to offer the needed capacity. However, in high cardinality systems, the 1D character of the spectral amplitude coding method restricts the reduction of multiple access interference and the related phase-generated intensity noise. In addition, dividing available spectral windows restricts support for large cardinality in zero or fixed-phase cross-correlation systems. As a result, for high transmission capacity and a large number of users across a long distance, a new dimension must be added to the existing 1D code. To include spatial encoding, currently employed 2D spectral amplitude coding-optical code division multiple access systems use spectral/spatial coding techniques that necessitate a significant number of optical fiber media between the transmission and reception modules. This severely affects the practicality of implementing 2D optical code division multiple access in a passive optical network. As a result, spectral/temporal coding has been optimized for low-cost passive optical networks. To support a high number of users while maintaining a low bit error rate, spectral/temporal coding is necessary. Based on current 1D multidiagonal and improved multidiagonal codes, this work proposes a unique 2-D spectral/temporal coding method. We do a thorough mathematical study using bit error rate, quality factor, and eye diagram as performance metrics. The system's performance shows that the code is efficient in terms of user count, multiple access interference, and encoder/decoder architecture.